Desarrollo de un sistema de Facturación bajo licencia GPL para las Pymes del Ecuador - Aldas, Ing. Clay (2010)
Billing System under the GPL for PyMEs of Ecuador, has developed under the DotNetNukeContent Management System (whichhas gates and modulesthat can be used for the website), aiso under the System Manager PostgreSQL database (database is open source) and the programming too! Visual Studio 2005 Express(C# Programming Language).Designed and Modeling under free tool like PowerArchitect Accounting transactions provide financial and administrative informatlon regarding sales, inventories, accounts receivable, revenues, costs, expenses, etc. It is a fundamen tal part of any accounting system; henee an accounting system is an organízed struc-ture through which the mformation is collected from a company as a result of its operations, using resources such as forms, reports, books and so on. And presented to management willallow it to make finandal decisions.Enterpr¡se(PYMES), aregrowingand ¡ncreasingly are discoveringneeds and essential requirements to improve attention to customers(user), to do research projects through the FreeSoftware will allow businesses to develop in a market ísfullyproductivo and competitivo while